On modified symmetric single-step procedure for estimating polynomial zeros simultaneously - Monsi, Mansor; Hassan, Nasruddin; M. Rusli, Syaida Fadhilah (Hikari, 2014)
The point symmetric single-step procedure PSS1 has R-order of convergence at least three. This method is modified, and calledthe midpoint symmetric single-step procedure PMSS1, so that a better rate of convergence is achieved. The convergence analysis of PMSS1 is shown along with its numerical results.